Electrochemical C(sp3)–H Fluorination - Takahira, Yusuke; Chen, Miao; Kawamata, Yu; Mykhailiuk, Pavel; Nakamura, Hugh; Peters, Byron K.; Reisberg, Solomon H.; Li, Chao; Chen, Longrui; Hoshikawa, Tamaki; Shibuguchi, Tomoyuki; Baran, Phil S. (Synlett, 2019)
A simple and robust method for electrochemical alkyl C–H fluorination is presented. Using a simple nitrate additive, a widely available fluorine source (Selectfluor), and carbon-based electrodes, a wide variety of activated and unactivated C–H bonds are converted into their C–F congeners. The scalability of the reaction is also demonstrated with a 100 gram preparation of fluorovaline.
Keywords: organic synthesis; electrochemistry; fluorination; C–H functionalization; radicals